RESPON MASYARKAT TERHADAP PROGRAM DESA MAJU INHIL JAYA (DMIJ) BIDANG SARANA INFRASTRUKTUR DIDESA PEKAN KAMIS KECAMATAN TEMBILAHAN HULU KABUPATEN INDRAGIRI HILIR - Tania Oktarina Azmi; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aimed to find out about the Response of Society Program Desa Maju Inhil Jaya Village (DMIJ) in the infrastructure sector. Where the community response is seen from 3 (three) aspects, namely cognitive response, affective response, and conative response. Given this, of course, will give a different response to the Desa Inhu Inhil Jaya Program. This research was conducted in Desa Pekan Kami, Kecamatan Tembilahan Hulu, Kabupaten Indragiri Hilir. To get the right research results, the authors used a quantitative descriptive method that was presented in tabular form and completed in detail, with a total sample of 77 respondents. The results showed that there was no significant effect between cognitive response and affective response to conative response to planning, implementation and maintenance. This is caused by other factors, namely development imperfections and policies implemented by the Village Government in involving the community in every activity. Inhil Jaya Advanced Program in Desa Pekan Kamis.   Keywords: Response, Society, Desa Maju Inhil Jaya Program